God, skepping en verlossing : 'n eksegetiese verkenning van Kolossense 1:13-20 (Afrikaans) - Van der Watt, J.G. (Jan Gabriel), 1952- (University of Pretoria, 2013)
Dissertation (PhD (New Testament Studies))--University of Pretoria, 2004.